Evaluating Crop Simulation Models Using Different Fertility Sources and Climate Model Outputs to Improve the Productivity of Sorghum - International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2020)
In the Sudanian region of Mali where sorghum is an important crop, inorganic fertilizer use is limited due to the high cost and limited availability, and limited soil moisture availability. However, fertilizers from livestock and poultry manure are largely available. This study evaluated different fertilizer response scenarios which will combine both organic and inorganic sources. Our target is to increase productivity (grain and biomass). Biomass so produced could further be used as a source of feed for the livestock and vice-versa. Furthermore, data collected from different agro-ecologies will be used to set up crop simulation models with climate model output of the Coupled Model Inter-comparison Project Phase 5 (CMIP5) to assess climate change impacts on sorghum yields and to evaluate the marginal cost-benefit of different fertility scenarios and varieties as adaptation options to climate change.